A timesaving, low-cost, high-yield method for the synthesis of ultrasmall uniform graphene oxide nanosheets and their application in surfactants. (16th December 2015) - Luo, Zhi-Jia; Geng, Hong-Zhang; Zhang, Xing; Du, Baotan; Ding, Er-Xiong; Wang, Jing; Lu, Zhanguo; Sun, Baoquan; Wang, Jie; Liu, Juncheng
Abstract: Graphene oxide nanosheets (GONSs) with a lateral size less than 100 nm have attracted more and more attention for their wide range of potential applications, from bionanotechnology and nanobiomedicine to surfactants. However, at present GONSs are commonly prepared from graphite nanofibers or graphite nanopowders which are both expensive. Here, a timesaving, low-cost, high-yield method is proposed for preparing ultrasmall uniform GONSs with an average lateral size of ∼30 nm, utilizing common graphite powder as the raw material in the absence of a strong acid. The obtained GONSs are able to disperse single-walled carbon nanotubes (SWCNTs) effectively, and the dispersion could withstand high-speed centrifugation. Consequently, GONSs could indeed serve as a superior surfactant for the dispersion of SWCNTs, and the dispersion could be further applied in electronics, as the GONSs may be further reduced to reduced GONSs or graphene nanosheets.